The Diversion of Prescription Opioid Analgesics - Inciardi, James A. (2007)
Prescription drug diversion involves the unlawful channeling of regulated pharmaceuticals from legal sources to the illicit marketplace, and can occur along all points in the drug delivery process -- from the original manufacturing site, to the wholesale distributor, the physician's office, the retail pharmacy, or the patient. Although a number of recent scientific papers have discussed the problems associated with diversion, empirical data on the scope and magnitude of diversion are limited in the literature. This paper presents findings from a national diversion survey being conducted as part of risk management initiatives supported by Denver Health and Hospital Authority, designed to monitor the abuse and diversion of a variety of prescription opioid analgesics. On a quarterly basis, diversion investigators in 300 jurisdictions distributed throughout the 50 states, the District of Columbia, and Puerto Rico are sent short questionnaires designed to elicit data on the extent of drug diversion in their areas. During the 20-quarter survey period reported in this paper, a total of 64,655 cases of prescription drug diversion were reported from all of the participating sites. The most widely diverted opioid was hydrocodone, in that it was mentioned in 38.2% of the cases, followed by oxycodone, mentioned in 24.3% of the cases. By contrast, the proportions of cases in which other opioids were mentioned were significantly smaller. The diversion of opioids appears in all 50 states, the District of Columbia, and Puerto Rico, with especially high concentrations in rural areas. How all of these prescription opioids are being diverted to the street, however, is not altogether clear, and in many ways, diversion is a “black box” requiring concentrated systematic study.